2017
DOI: 10.1038/ncomms14880
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic hot electron transport drives nano-localized chemistry

Abstract: Nanoscale localization of electromagnetic fields near metallic nanostructures underpins the fundamentals and applications of plasmonics. The unavoidable energy loss from plasmon decay, initially seen as a detriment, has now expanded the scope of plasmonic applications to exploit the generated hot carriers. However, quantitative understanding of the spatial localization of these hot carriers, akin to electromagnetic near-field maps, has been elusive. Here we spatially map hot-electron-driven reduction chemistry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
463
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 378 publications
(479 citation statements)
references
References 57 publications
16
463
0
Order By: Relevance
“…Meanwhile, energy transfer can also occur from the TSPR to the LSPR mode, which is promoted by electron–hole pairs . Furthermore, it is suggested that the maximum hot electron flux occurs at the tip of the plasmonic nanostructures and the flux decays exponentially far from the tip . Therefore, the hot electrons with lower energy (generated after multiple scattering) possess longer mean free paths and high energetic electrons remain localized closer to the field hotspots .…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…Meanwhile, energy transfer can also occur from the TSPR to the LSPR mode, which is promoted by electron–hole pairs . Furthermore, it is suggested that the maximum hot electron flux occurs at the tip of the plasmonic nanostructures and the flux decays exponentially far from the tip . Therefore, the hot electrons with lower energy (generated after multiple scattering) possess longer mean free paths and high energetic electrons remain localized closer to the field hotspots .…”
Section: Resultssupporting
confidence: 66%
“…Pure Au NRs were synthesized using the seed‐mediated method originally developed by Murphy and co‐workers, and later modified by El‐Sayed and Nikoobakht . Briefly, seed solution was prepared by adding a freshly prepared, ice‐cold aqueous solution of NaBH 4 (Sigma‐Aldrich, 0.6 mL, 0.01 m ) into a solution of HAuCl 4 ·3H 2 O (Sigma‐Aldrich, 0.025 mL, 0.1 m ) and C 16 TAB (bioreagent grade, Sigma‐Aldrich, 10 mL, 0.1 m ).…”
Section: Methodsmentioning
confidence: 99%
“…Zhang et al investigated the concentration dependence of pNTP molecules,and observed that azo bond formation had occurred on the sample with high molecular density,a nd that plasmon-induced dissociation from pNTP to thiophenol had occurred for the lower molecular density. [56] The dissociation of the azo bond was induced by the combination of the hot electrons and tunneling electrons,w hich was demonstrated using STM-TERS. reported that the reduction from pNTP to pATPinanacid halide media (HCl, HBr, and HI) was driven by hot-electron transfer.…”
Section: Indirect Hot-electron Transfer Mechanism 331 Formation Ofmentioning
confidence: 99%
“…The high sensitivity of SERS is mostly due to the local electromagnetic field enhancement in “hotspots” (nanoscale regions where hot electrons primarily appear). Unfortunately, the enhancement in the randomly distributed hotspots on an SERS substrate can vary enormously.…”
Section: Introductionmentioning
confidence: 99%